Índices de rentabilidad en la empresa Mastertub S. A en los periodos 2020 y 2021. - Morales Loor, Nathali Elizabeth (2022)
Profitability is one of the most important aspects in any type of organization, for this reason, companies seek to optimize their resources to get the most out of them and achieve success. However, currently there are still shortcomings in administrative management that prevent increasing profitability levels, a situation that reveals the lack of concern that certain organizations have in developing adequate financial management. Reason for which, the objective of this case study is to measure the level of profitability of the company Mastertub .S.A through financial indicators for the periods 2020 and 2021. The methodology used in the research consisted of a mixed approach: qualitative-quantitative and the types of research used were documentary and descriptive, while the methods used are deductive and inductive. Direct observation was also determined as techniques with the intention of collecting the greatest amount of information related to the problem studied. The results showed that inadequate financial management carried out in Mastertub S.A limits the timely detection of problems that cause the low rate of profitability in the company. One of the main problems for which optimal profitability is not achieved is that the organization does not carry out analyzes of financial indices in an effective way that helps to understand the situation of the company and make the right decisions that contribute to its growth. It was concluded that the profitability of Mastertub S.A in the year 2021 was negative.